Aquisição do vocabulário e da fonologia do português brasileiro - Wiethan, Fernanda Marafiga (2015)
This research aimed to analyze the phonology and vocabulary behavior in children with typical language development and to verify the correlations between these language components. 186 children aged from 1:6 to 5:11;29, who were Brazilian Portuguese speakers, with typical language development took part in this research. The data collection involved speech, language and hearing assessments and spontaneous speech recordings. The phonology was assessed regarding to the number of acquired consonants in the general phonological system, in each syllabic structure, in Implicational model of feature complexity (IMFC) levels and sound classes. The vocabulary was assessed as to number of produced types, tokens and word classes. These data were compared among the ages. After, the correlations among the types produced and the variables set to the phonological system and between word classes and sound classes were calculated in each age. The correlation significance was also calculated. Nouns and verbs were prevalent in all ages. The production of the word classes increases with the age except onomatopoeias and interjections. In general, the types produced also present increase with the age. The phonological acquisition was similar to other Brazilian researches. Stops and nasals are acquired first, followed by fricatives and liquids. Different positive correlations were found among the types produced and the consonants, syllabic structures and IMFC levels. Only one negative correlation was found between the number of types and the complex onset in the last age analyzed. Regarding to the correlations between the word classes and sound classes, the positive correlations were prevalent, and they occurred more in the first age groups. Most of the negative correlations were found in the intermediate age groups. The nasals didn't have correlations with the word classes and the stops had only positive correlations. The fricatives presented more significant correlations with different word classes than other sound classes. Few significant correlations between the word classes and the liquids occurred and most of them were negative. In conclusion, the phonological acquisition of Brazilian Portuguese starts with stops and nasals, so fricatives and liquids are more marked. The phonological system present a gradual growing with few regressions. In general, the acquisition of vocabulary occurs as a growing process. Nouns and verbs are prevalent and they are the first words produced by the children. The words more related to syntax, such as conjunctions, are acquired later and have slower improvement. The word classes are more produced according to age, except onomatopoeias and interjections. Most of the correlations between vocabulary and phonology were positive, which indicates that these two systems are interdependent. The negative correlations were related to complex onset and to the most complex word classes and sound classes. These negative correlations point to the influence of phonological complexity and syntax in the vocabulary acquisition.